PREPARATION OF REFLECTIVE PEDAGOGY PARADIGM LEARNING FOR THE LECTURERS BASED ON COMPUTATIONAL CHEMISTRY - Yuliyanto, Eko; Hidayah, Fitria Fatichatul; Istyastono, Enade Perdana; Wijoyo, Yosef; Hartayu, Titien Siwi (Unnes Science Education Journal, 2019)
The study aims to prepare lecturers on reflective pedagogy paradigm (RPP). This research was a mixed method. It was conducted with nine students and a model lecturer (mantee) who underwent mentoring. It was held in 4 meetings and observed by two observers. The assessment was conducted using data triangulation to a model lecturer based on video recording, reflection by mantee and students. The measure of process success was based on video recordings by ≥70%. The lecturer’s reflection to demonstrate the readiness in the teaching, and the student’s reflection is ≥ 60%. The results of mantee and student at every stage are: 81%, 69%, 88%, and 50%; 72%, 92%, 73%, and 85% of context, experience, reflection, and action. The results of the evaluation there was a significant difference before and after the learning based on RPP (p = 0.035). So, mentees was able to manage RPP and able to make students active to learn from theory to practice.